Zasady ogólne wymiany informacji podatkowych z innymi państwami - Mazur, Anna; Kowalczyk-Wodzińska, Jolanta (Kwartalnik Prawa Publicznego, 2012)
Free movement of goods and services, persons and capital within the European Union brings not only positive effects, but also challenges for member states’ authorities connected i.a. with the risk of avoiding tax payment by EU citizens and companies. In order to meet this challenge, tax authorities of the member states started up a broad cooperation, which includes also the exchange of information concerning all tax and other public duties relevant cases. The article describes legal regulations concerning the cooperation between the member sates’ authorities in relation to exchange of tax relevant information, not only on national and EU, but also on international level. The scope of the article is to point out the significance of the information exchange in tax cases, as well as an analysis, when and how far the information gained through cooperation with foreign tax authorities may be used in domestic tax cases and proceedings.